Hydrotherapy in canine patients - Kangas, Petra (SLU/Dept. of Clinical Sciences (until 231231), 2016)
Hydrotherapy in canine patients is becoming increasingly more common. This literature study's objective is to gather information about this therapy method in dogs: how it works, when it is to be used, what is needed for successful aquatic therapy and how the outcome assessment can be made. 42 publications were used to gather information. The target group for the study is veterinary nurses and veterinary nursing students, especially the ones interested in working within the field of rehabilitation. The two types of hydrotherapy that are used for rehabilita-tion are swimming and using an underwater treadmill. Most of the effects achieved are due to properties of water, which include hydrostatic pressure, buoyancy, viscosity, surface tension and warmth. There are many different indications for using hydrotherapy but most of them are either orthopaedic or neurological. General conditioning is also possible as well as using aquatic therapy as palliative care due to its analgesic effect. To achieve the best possible re-sults, hydrotherapy has to be tailored individually when it comes to for example the depth of the water and the length of the exercise. The patient should be monitored closely. Outcome assessment should be made in walk, trot and even gallop as long as it is safe for the patient. It is important to evaluate function even in rest. Multiple different tools can be used to aid in the outcome assessment, such as a goniometer, measuring devices and x-ray. The therapist can do the initial evaluation but the success of the treatment should always be monitored by a veteri-nary surgeon as well. Staff working with rehabilitation should have knowledge of all the fac-tors affecting the hydrotherapy process for the best possible outcome. More research is re-quired in this field of veterinary medicine for better understanding.